Schopenhauer and the Later Schelling in Dialogue on Mythology and Religion - Auweele, Dennis vanden (The journal of religion, 2017)
The article examines the views of philosophers Arthur Schopenhauer and Friedrich Wilhelm Joseph von Schelling on the relationship between religion and mythology. Topics include the differences and similarities between both men's philosophy, their opposition to Hegelian dialectical philosophy, and their relationship to Romanticism. Also discussed are their engagement on religion and mythology and the lack of truth in mythology for both philosophers.